The Construction and Practice of the Undergraduate Teaching System of New Media Technology - Chao, Jilei (Pacific International Journal, 2024)
With the rapid development of new technologies such as mobile internet, big data, and artificial intelligence, new media has become an important force in the communication field. It is imperative to build a complete undergraduate teaching system of new media technology and cultivate versatile talents to meet the needs of industry development. Taking the majors of new media technology and new media (big data news communication direction) at Qilu University of Technology as an example, this study analyzes the issues in talent training objectives, curriculum setting, teaching content and teaching methods through literature review, questionnaires and interviews. It is proposed to build a modularized and flexible curriculum system oriented to ability training, increase cutting-edge new media technology courses, and strengthen the cultivation of software and hardware platform application abilities. In terms of teaching methods, project-driven teaching methods are implemented, distinctive project training courses are set up to promote knowledge application and comprehensive ability training. The research shows that building an open, flexible undergraduate teaching system of new media technology that emphasizes cross integration will help improve the quality of talent cultivation and enable talents to better meet the needs of new media industry development. This study provides theoretical support and practical approaches for promoting the teaching reform of the new media technology major.